We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
202
1
avatar+23 

Let $r$ and $s$ be the roots of $x^2 - 6x + 2 = 0.$ Find $(r - s)^2.$

 Jan 27, 2019
 #1
avatar+104069 
+1

x^2 - 6x + 2 = 0

 

x^2 -6x + 9  = -2 + 9

 

(x - 3)^2 =  7   take both roots

 

x - 3 =   ±√7

 

x = √7 + 3        or   x = -√7 + 3

 

So   ( r -s) =   2√7  =   √28

 

So   (r - s)^2   =    28

 

 

cool cool cool

 Jan 27, 2019

12 Online Users